2022
DOI: 10.3389/fmicb.2022.787146
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Changes in 26,500-Year-Old Thawing Permafrost

Abstract: Northern permafrost soils store more than half of the global soil carbon. Frozen for at least two consecutive years, but often for millennia, permafrost temperatures have increased drastically in the last decades. The resulting thermal erosion leads not only to gradual thaw, resulting in an increase of seasonally thawing soil thickness, but also to abrupt thaw events, such as sudden collapses of the soil surface. These could affect 20% of the permafrost zone and half of its organic carbon, increasing accessibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 104 publications
4
19
2
Order By: Relevance
“…This could enable dispersal into deeper soils, although we expect this to be an overall slow process as we expect an overall still low soil temperature and nutrient availability. An amplicon-based study at this site still confirmed similar emerging drivers, mainly layer and age (Scheel et al, 2022), as the only soil microbial studies performed locally before (Ganzert et al, 2014; Gittel et al, 2014b). Overall, more than half of all counts stem from taxa dominantly present in the thawed layers.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…This could enable dispersal into deeper soils, although we expect this to be an overall slow process as we expect an overall still low soil temperature and nutrient availability. An amplicon-based study at this site still confirmed similar emerging drivers, mainly layer and age (Scheel et al, 2022), as the only soil microbial studies performed locally before (Ganzert et al, 2014; Gittel et al, 2014b). Overall, more than half of all counts stem from taxa dominantly present in the thawed layers.…”
Section: Discussionsupporting
confidence: 57%
“…Similarly, the active Bacteroidetes order Sphingobacteriales dominated recently thawed permafrost. In our study site, this order formerly had the highest relative amplicon-based abundance with more than 50% of all counts between 70‒90 cm depth in 2020, despite very low abundances one year earlier (Scheel et al, 2022). This confirms that this taxon as a major component of the microbial community at thawed depths, which responds strongly to thaw (Burkert et al, 2019; Coolen and Orsi, 2015; Deng et al, 2015; Frank-Fahle et al, 2014) and is abundant at the upper permafrost limit (Müller et al, 2018; Tripathi et al, 2018).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations